FAKTOR RISIKO STRES KERJA PADA PEKERJA PROYEK PEMBANGUNAN SUDETAN KALI CILIWUNG-KANAL BANJIR TAHUN 2022 - Marissa Lisa Arvianti (2022)
Job stress is not something new. Three out of five people stated that work stress can be directly related to acute and chronic health problems, so that work stress is characterized as a disease in the 20th century. The purpose of this study was to analyze the risk factors for work stress in workers in the Ciliwung River-Kanal Flood East Sudetan Project. The research method is analytic-quantitative using cross-sectional method. The population in this study were 150 workers and the number of samples was 114 workers. The research time starts from April to June 2022. The statistical test used is the Chi-Square test. The results of the analysis showed years of service (p-value = 0.009; POR = 4.015; 95% CI = 1.493 - 10.794), education level (p-value = 0.002); POR= 6.432; 95% CI = 2.005 - 20.635), and the relationship between workers (p-value = 0.016; POR = 4.059; 95% CI = 1.372 - 12.004) had a significant association with work stress. Therefore, the workplace can give appropriate appreciation to workers who perform well and also build communication between organizations by providing support when workers provide suggestions.